Depression and suicidality in HIV/AIDS in China - Jin, Hua; Hampton Atkinson, J.; Yu, Xin; Heaton, Robert K.; Shi, Chuan; Marcotte, Thomas P.; Young, Corinna; Sadek, Joseph; Wu, Zunyou; Grant, Igor (Journal of affective disorders, 2006)
This pilot study examined rates of major depression and suicidality and their associations with daily functioning in HIV infected (HIV+) and uninfected (HIV−) persons in China. HIV+ participants ( N = 28) and demographically matched HIV− controls ( N = 23) completed the Chinese Composite International Diagnostic Interview to determine lifetime rates of major depressive disorder (MDD) and suicidality. Current mood and suicidal ideation were assessed with the Beck Depression Inventory-I. The impact of depression and HIV infection on daily functioning was measured by an Activity of Daily Living questionnaire. Mean duration of known HIV+ status was 2 years. Almost 79% ( n = 22) of HIV+ but just 4% ( n = 1) of HIV− groups reported lifetime major depression. Of the 22 HIV+ individuals with lifetime MDD, only one had onset before learning of HIV status. The remainder developed MDD within 6 months after testing HIV positive. In those HIV+ subjects who met MDD criteria after HIV diagnosis, only two (9%) had received depression treatment, yet four (18%) had persisting active suicidal thoughts. Depression and HIV+ status independently predicted worse daily functioning. Representativeness is limited in this small sample of convenience. This preliminary study presents evidence of high rates of major depression and suicidality in HIV-infected persons in China. Despite this, few had sought mental health assistance, suggesting a need to increase awareness of psychiatric comorbidity and access to mental health services.